2013
DOI: 10.2478/jppr-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Immunoliogical Responses of Hyphantria Cunea (Drury) (Lepidoptera: Arctiidae) to Entomopathogenic Fungi, Beauveria Bassiana (Bals.-Criy) and Isaria Farinosae (Holmsk.) Fr.

Abstract: Abstract:Five morphological types of hemocytes were recognized in hemolymph of the 4th instar larvae of Hyphantria cunea (Drury). These hemocytes were: prohemocytes, plasmotocytes, granulocytes, oenocytoids, and spherulocytes. Tests were done on the effects of four isolates of the entomopathogenic fungus Beauveria bassiana (Bals.-Criy) (Fashand, spt-22, Ir-K-40 and 566), one isolate of Isaria farinosae (Holmsk.) Fr. (1872c), and latex-beads on the cellular immune defense mechanism and Phenoloxidase (PO) activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A number of studies on the use of some entomopathogenic fungi against the H. cunea (Sullivan et al, 2011;Iskender et al, 2012;Qin et al, 2012;Ajamhassani, 2013;Zibaee et al, 2013) were reported in the world. Three isolates of B. bassiana tested on larvae of H. cunea caused mortality between 90±5.77% and 96.6±3.33% (Iskender et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on the use of some entomopathogenic fungi against the H. cunea (Sullivan et al, 2011;Iskender et al, 2012;Qin et al, 2012;Ajamhassani, 2013;Zibaee et al, 2013) were reported in the world. Three isolates of B. bassiana tested on larvae of H. cunea caused mortality between 90±5.77% and 96.6±3.33% (Iskender et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many EPF species have been detected in various insect species and found to be highly effective (Ansari et al 2008, Xiong et al 2013 Nowadays, many studies have shown that EPFs are effective in controlling H. cunea (Sullivan et al 2011, Qin et al 2012, İskender et al 2012, Ajamhassani 2013, Zhang et al 2016, Aker and Tuncer 2016a, 2016b, Saruhan et al 2017, Wang et al 2020, Karabörklü et al 2020, 2022. The present study showed that two indigenous B. bassiana strains have significant pathogenic activity against H. cunea.…”
Section: Discussionmentioning
confidence: 99%
“…Khosravi et al (2012) used SEM to identify five types of hemocytes in all larval instars of the carob moth Ectomoyelois ceratoniae: PRs, PLs (with several morphological forms), GRs, SPs, and OEs. Ajamhassani et al (2013) identified five hemocyte types in haemolymph of the 4 th instar larvae of the fall webworm Hyphantria cunea, without ADs, whereas Zibaee and Sendi (2011) used LM and recognized six types: PRs, PLs, GRs, OEs, SPs and ADs in the same insect. Five hemocyte types had been reported in the Mediterranean flour moth Ephestia kuehniella: PRs, PLs GRs, EOs and SPs (Ghasemi et al, 2013a) while Ghasemi et al (2013b) distinguished two additional morphotypes, namely VEs and POs in haemolymph of this species.…”
Section: Categorization Of Circulating Hemocyte Types In Insectsmentioning
confidence: 99%